2012
DOI: 10.1186/1756-0500-5-248
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of breast cancer-associated genes between stage- and age-matched tumor specimens from African- and Caucasian-American Women diagnosed with breast cancer

Abstract: BackgroundRecent studies suggest that the poorer breast cancer outcome observed in African-American women (AAW) may, in part, result from underlying molecular factors. The purpose of this study was to investigate gene expression differences between Caucasian-American women (CAW) and AAW that may contribute to this poorer prognosis.MethodsThe expression of 84 genes involved in breast carcinoma prognosis, response to therapy, estrogen signaling, and tumor aggressiveness was assessed in age- and stage-matched CAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 95 publications
3
26
0
Order By: Relevance
“…This comparison was our only comparison where ESR1 was differentially expressed between AA and CA samples, and Grunda et al saw a similar decrease in expression of ESR1 in their study [21]. We believe this finding suggests that AA women may have reduced ER expression in later stages or that AA women may be more susceptible to mutations causing the ER- phenotype.…”
Section: Discussionsupporting
confidence: 69%
“…This comparison was our only comparison where ESR1 was differentially expressed between AA and CA samples, and Grunda et al saw a similar decrease in expression of ESR1 in their study [21]. We believe this finding suggests that AA women may have reduced ER expression in later stages or that AA women may be more susceptible to mutations causing the ER- phenotype.…”
Section: Discussionsupporting
confidence: 69%
“…While aggressive forms of BC disproportionately affect AA women, this does not fully explain the disparities; even within subtype there are differences in survival by race. From previous studies we have learned that: 1) survival differences exist between AA and CAU despite equal treatment [5] or tumor subtype [3] and 2) genes are differentially expressed between AA and CAU tumors even when matching on clinical features [6, 7, 9]. Genes that are both differentially expressed by race in tumors, and confer a survival disadvantage could explain a portion of the observed racial survival disparity, although to date no study had evaluated whether race-associated genes conferred a survival disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that independent of ER status, 19 and eight genes were differentially expressed in the breast tumor stroma and epithelium, respectively, of 18 AA and 17 CAU women. Grunda et al [7] evaluated expression of 84 genes associated with breast cancer aggressiveness, prognosis and response to therapy, and found that 20 of these genes were differentially expressed in 12 AA and 12 CAU age- and stage-matched breast tumors. Field et al [6] identified genes that were differentially expressed in 26 AA and 26 CAU age, grade and ER-matched breast tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Black women with HR positive breast cancer have a much higher mortality rate in the first two years after diagnosis than whites,[34] but among those with TNBC, there is conflicting data on survival outcomes according to race. [16, 19, 21, 26, 28, 29, 33, 34] Although studies in breast cancer patients in general have identified racial differences in genomic profiles,[10, 13] it is unclear if these differences are being driven by those with HR positive cancers or TNBC. To address this lack of data, we sought to investigate racial differences in the genetic landscape of TNBC.…”
Section: Introductionmentioning
confidence: 99%